Intra-family relationships of generation in Belarus - Dmitrieva, Olga E. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The features of socialization of the elderly, as well as problems and risks at this stage, such as the lack of clearly defined roles, social exclusion, deprivation, ageism, are considered. It also presents the results of research of intergenerational relationships in the modern Belarusian family, conducted in the framework of the survey «Belarus: family formation, stability of family relations and fertility in changing socio-economic conditions» (2017). The object of the research was citizens of the Republic of Belarus over 18 years old (9996 people). The results show that the relationship between elderly people and their grown up children in Belarusian families are still built within the framework of traditional family values, meaning intergenerational relationships remain close enough, and older parents and their children are ready to take care of each other. Older generations help young people in caring for children and support them financially. Young people take care of their parents, helping them with household chores and personal care.